Selective transarterial embolization for posttraumatic renal hemorrhage: a second try is worthwhile - Huber, Johannes; Pahernik, Sascha; Hallscheidt, Peter; Sommer, Christof-Matthias; Wagener, Nina; Hatiboglu, Gencay; Haferkamp, Axel; Hohenfellner, Markus (The journal of urology, 2011)
Purpose: - - Selective percutaneous transarterial embolization has proved to be effective, safe treatment for posttraumatic renal hemorrhage but inefficacious procedures often lead to nephrectomy. Thus, the success rate of transarterial embolization should be maximized. - - Material and Methods: - - We retrospectively investigated the clinical success rate of transarterial embolization for posttraumatic bleeding. Study inclusion criteria were imaging evidence and clinical signs of hemorrhage or a hemoglobin decrease of more than 2 gm/dl in urological cases. We excluded spontaneous bleeding from analysis. - - Results: - - A total of 21 patients with a median age of 66 years (range 12 to 78) met study inclusion criteria. Etiology was blunt trauma in 3 cases (14%), stab wound in 1 (5%) and an iatrogenic cause in 17 (81%). In 2 patients an active bleeding site could not be detected during selective angiography. Transarterial embolization was done in 19 patients and led to primary clinical success in 12 (63%), including 2 with grade V parenchymal injury. In 6 of 7 cases (86%) in which primary treatment failed transarterial embolization was repeated. It resulted in clinical success in 4 of 6 patients (67%) with equal efficiency (p =1). Three patients (16%) who could not be sufficiently treated with transarterial embolization underwent nephrectomy. - - Conclusions: - - When conservative measures fail and clinical symptoms or a relevant hemoglobin decrease occur, transarterial embolization should be considered. Since the success rate is equally high for initial and repeat interventions, re-intervention is justified when the clinical course allows.
Gesehen am 30.06.2022